2017
DOI: 10.1038/s41598-017-11607-0
|View full text |Cite
|
Sign up to set email alerts
|

General Anesthetics Regulate Autophagy via Modulating the Inositol 1,4,5-Trisphosphate Receptor: Implications for Dual Effects of Cytoprotection and Cytotoxicity

Abstract: General anesthetics are both neuroprotective and neurotoxic with unclear mechanisms. General anesthetics may control cell survival via their effects on autophagy by activation of type 1 inositol triphosphate receptor (InsP3R-1). DT40 or SH-SY5Y cells with only or over 99% expression of InsP3R-1 were treated with isoflurane or propofol. Cell viability was determined by MTT reduction or LDH release assays. Apoptosis was determined by measuring Caspase-3 or by TUNEL assay. Autophagy activity was determined by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 60 publications
1
32
0
Order By: Relevance
“…Isoflurane was shown to directly open InsP3R channels to induce excessive Ca 2+ release from ER into cytosol and mitochondria, which further leads to mitochondrial calcium overload, ATP production failure, cytochrome C release and caspase activation [ 20 22 ]. In addition to targeting the mitochondria, recent data suggests that GA-induced cytosolic calcium buildup also impairs autophagosomal and autolysosome function to reduce cytoprotective autophagy, which would bias cell towards apoptosis [ 23 ] (Fig. 1 ).…”
Section: The Developing Brainmentioning
confidence: 99%
“…Isoflurane was shown to directly open InsP3R channels to induce excessive Ca 2+ release from ER into cytosol and mitochondria, which further leads to mitochondrial calcium overload, ATP production failure, cytochrome C release and caspase activation [ 20 22 ]. In addition to targeting the mitochondria, recent data suggests that GA-induced cytosolic calcium buildup also impairs autophagosomal and autolysosome function to reduce cytoprotective autophagy, which would bias cell towards apoptosis [ 23 ] (Fig. 1 ).…”
Section: The Developing Brainmentioning
confidence: 99%
“…Therapies targeting cellular Ca 2+ pathways have demonstrated anti-tumor efficacy in vitro. Volatile anesthetics, such as sevoflurane, isoflurane, and desflurane, and propofol activate Ca 2+ receptors [17,18] including TRPV1, which is sensitized by exposure to inhaled anesthetics [19]. We hypothesized that the highly selective plasma membrane Ca 2+ channel, TRPV1, may mediate the observed effects of general anesthetics.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies suggested that propofol can regulate cell autophagy via activation of InsP 3 (InsP 3 R) or ryanodine receptors (RYR) [ 15 , 16 ], with unclear mechanisms. Calcium may also be involved in autophagy by affecting ATG5.…”
Section: Introductionmentioning
confidence: 99%